CHALLENGES OF DISTANCE EDUCATION DURING THE SCHOOL LOCKDOWN: THE LITHUANIAN SCHOOL LEADERS’ PERSPECTIVE - Kaminskienė, Lina; Chu Ling, Yi (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The COVID19 pandemic has caused massive disruption in education practices worldwide and Lithuania was no exception. This article investigates how this period of uncertainties has been perceived by Lithuanian schools during school lockdown. The study aimed to explore the challenges that Lithuanian schools faced and how distance education practices has been reconsidered during school lockdown. The research was based on a survey of 406 sampled school leaders of public education institutions in Lithuania conducted two months into the first nationwide lockdown in spring 2020. This paper aims to discuss the challenges of distance education from the perspective of school leaders, and to link the findings of the study to recent studies related to schools’ responses to the pandemic situation. The survey responses indicated that schools initially focused on the organisation of staff training and technological preparation to start distance education during the first two weeks of lockdown. Their focus two months into the process shifted towards tackling challenges on students' responsiveness and assessment of students' achievements during distance education. Challenges are perceived as opportunities for reflection and growth, re-examine current institution strengths and weaknesses, and reconsolidate with the school communities in prioritising what the utter function in education is.